Numerical Approach to the Plasmonic Enhancement of Cs2AgBiBr6 Perovskite-Based Solar Cell by Embedding Metallic Nanosphere - Kyeong-Ho Seo; Xue Zhang; Jaehoon Park; Jin-Hyuk Bae (Nanomaterials, 2023)
Lead-free Cs2AgBiBr6 perovskites have emerged as a promising, non-toxic, and eco-friendly photovoltaic material with high structural stability and a long lifetime of carrier recombination. However, the poor-light harvesting capability of lead-free Cs2AgBiBr6 perovskites due to the large indirect band gap is a critical factor restricting the improvement of its power conversion efficiency, and little information is available about it. Therefore, this study focused on the plasmonic approach, embedded metallic nanospheres in Cs2AgBiBr6 perovskite solar cells, and quantitatively investigated their light-harvesting capability via finite-difference time-domain method. Gold and palladium were selected as metallic nanospheres and embedded in a 600 nm thick-Cs2AgBiBr6 perovskite layer-based solar cell. Performances, including short-circuit current density, were calculated by tuning the radius of metallic nanospheres. Compared to the reference devices with a short-circuit current density of 14.23 mA/cm2, when a gold metallic nanosphere with a radius of 140 nm was embedded, the maximum current density was improved by about 1.6 times to 22.8 mA/cm2. On the other hand, when a palladium metallic nanosphere with the same radius was embedded, the maximum current density was improved by about 1.8 times to 25.8 mA/cm2.